2018
DOI: 10.1287/mnsc.2017.2790
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Consumer Search Cost on Assortment Planning and Pricing

Abstract: Consumers search for product information to resolve valuation uncertainties before purchase. We incorporate search cost into consumer choice models and study the two-stage consider-then-choose policy. In the first stage, a consumer forms her consideration set by balancing utility uncertainty and search cost. In the second stage, she evaluates all products in her consideration set and chooses the one with the highest net utility. We show that the revenue-ordered assortment (i.e., the offer set that includes pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(50 citation statements)
references
References 33 publications
2
48
0
Order By: Relevance
“…This heuristic is optimal in the case of the MNL, even with a capacity constraint. Wang and Sahin (2018) has studied the assortment optimization in a context in which consumer search costs are non-negligible. The authors showed that the strategy of revenue-ordered assortments is not optimal.…”
Section: Relevant Literaturementioning
confidence: 99%
“…This heuristic is optimal in the case of the MNL, even with a capacity constraint. Wang and Sahin (2018) has studied the assortment optimization in a context in which consumer search costs are non-negligible. The authors showed that the strategy of revenue-ordered assortments is not optimal.…”
Section: Relevant Literaturementioning
confidence: 99%
“…An assumption made in our paper is that the number of stages a customer is willing to interact is known when she arrives; this is also assumed in the papers above (and in some cases, assumed to always equal two). Other models have been proposed when a single customer views a variable number of pages; see (Gallego et al 2018), and also (Wang and Sahin 2017) who models the "search cost" paid by the customer to view more pages.…”
Section: Comparison Of Model To Related Literaturementioning
confidence: 99%
“…Therefore, the emphasis of our work is quite different from these papers. Wang and Sahin (2018) consider an assortment optimization problem under a consider-then-choose model. The consideration set in the consider-thenchoose model is formed by customers deciding to research a subset of the products to ascertain the valuations of those products.…”
Section: Literature Reviewmentioning
confidence: 99%